The effect of the use of vacuum therapy and instillation of L-arginine in the treatment of purulent wounds on the activity of nitric oxide cycle enzymes - T.V. Horodova-Andrieieva; O.Ye. Akimov; V.O. Kostenko; O.H. Krasnov; V.I. Lyakhovskyi; M.I. Kravtsiv (Медицина неотложных состояний, 2025)
Background. The problem of treating purulent wounds remains one of the most urgent throughout the history of surgery. Nowadays, despite many years of experience and constant scientific research, the problem of diagnosis and treatment of purulent wounds does not lose its relevance. The purpose is to evaluate the effect of vacuum therapy and instillation of L-arginine in the treatment of a purulent wound on the production of nitric oxide by different isoforms of NO-synthase and the activity of the arginase pathway of L-arginine metabolism. Materials and methods. The experiment was conducted in 20 patients who were randomly divided into 2 groups: vacuum therapy (GR-1, n = 10) and vacuum therapy with instillations of L-arginine solution (GR-2, n = 10). In the blood plasma, the following parameters were investigated: total activity of NO-synthase, activity of the inducible and constitutive isoforms of NO-synthase, activity of arginases and nitrite concentration. Results. When comparing the results obtained after the treatment of a purulent wound in patients from GR-1 and GR-2, a statistically significant difference was found in the concentration of nitrites and the activity of arginases. Thus, the concentration of nitrites in the venous blood of GR-2 patients after treatment of a purulent wound was 45.59 % lower than in GR-1. The activity of arginase in the blood plasma taken from the venous bed closest to a purulent wound was 25.23 % higher in patients with GR-2 compared to the indicators in GR-1. Conclusions. Vacuum therapy with L-arginine instillation, in addition to the effects of therapy itself, limits the accumulation of nitrites in the blood of the venous bed closest to a purulent wound and enhances the metabolism of L-arginine by the arginase pathway.